Strengthening Character Education Through Islamic Religious Education: A Case in Indonesian Context - Furqon, Ahmad; Hanif, Ma'mun (Tadibia Islamika: Journal of Holistic Islamic Education, 2022)
The school is one of the strategic places for forming character, family, and society. This is what underlies the need for a character education program in a school, intra-curricular, co- curricular, and extracurricular activities. The purpose of this study is to find out what kind of character-strengthening strategies can build student character based on the values of Islamic teachings. This type of research is qualitative research. Data collection techniques used observation, interviews, and documentation. The results of the study showed that strengthening character education through Islamic religious education at SMPN 01 Pemalang includes class-based character education in the form of a child's psychological approach, school-based character education in the form of lesson plan preparation that can form good character to students, community-based character education is implemented in activities in student extracurriculars, such as Rohis. In addition, character education is also carried out through guidance and counselling. From this implementation stage, it can be said that the spirit of character education has been appropriately implemented and optimally to have a good effect on students' character.